Anti-Bacterial and Anti-Fungal Activities from Macaranga bancana Leaves Extract - Rianti Putri; Rudi Hendra; Hilwan Y. Teruna (Universitas Padjadjaran, Indonesia)
Macaranga bancana is one of the Indonesian medicinal plants that is empirically used to treat infectious disease. The aim of this study was to evaluate anti-bacterial and anti-fungal activities of M. bancana against human pathogenic microbes, i.e., Escherichia coli, Staphylacoccus aureus, and Candida albicans. The dried leaves of M. bancana were extracted using cold extraction method with n-hexane, dichloromethane, ethylacetate, methanol, and ethanol solvents. The evaluation of anti-microbial activity from these extracts at the concentration of 1000 µg/ml was conducted using microdilution method. Amoxicillin, cephadroxil, and ketoconazole were used as positive controls. All extracts showed 100% inhibitory activity against S. aureus, with the exception of ethanol extract which was 72.8%. Nevertheless, methanol and ethanol extracts showed 100% inhibitory activity against E. coli, while the lowest activity was shown by n-hexane extract ( 45.2%). All extracts exhibited 100% inhibitory activity against C. albicans. In conclusion, leaves extract of M. bancana is a potential source of anti-bacterial and anti-fungal agents. Keywords: anti-bacterial, anti-fungal, M. bancana, microdilution